Relating benthic sensitivity and status to spatial distribution and intensity of trawling in the Eastern Mediterranean. (June 2023) - Smith, Christopher J.; Papadopoulou, Nadia K.; Maina, Irida; Kavadas, Stefanos; van Denderen, P. Daniel; Katsiaras, Nikolaos; Reizopoulou, Sofia; Karakassis, Ioannis; Tselepides, Anastasios; Tsikopoulou, Irini
Graphical abstract: Highlights: Environmental protection linked to EU policy implementation requires benthic status assessments at the habitat level. Bottom trawling operates over many habitats but with different intensity. Relative benthic status values were above the threshold of 0.95 for all habitats analysed. The assessment allows us to identify areas and habitats that are most at risk, and to prioritize management actions. Abstract: The ecosystem approach to fisheries management needs information of not just where bottom trawlers operate but also on their impact on the seabed, which is also highly relevant to the EU Marine Strategy Framework Directive (MSFD) Descriptor D6, seafloor integrity. In this study, we assess the benthic impact of bottom trawling in the Eastern Mediterranean in areas primarily fished by the Greek fleet. Seabed habitat sensitivity was modelled using macrofaunal longevity and biomass relationship based on data from more than 800 locations, representing 9 MSFD benthic habitats, and benthic status was assessed using the relative benthic status indicator. The pressure of seabed trawling was higher in circalittoral mud and circalittoral sand habitats showing a heterogeneous distribution pattern with intensive trawling in localized areas mainly coastal. Benthic status was high for all habitats reflecting the low trawling intensity and impact in most of the study area compared to other regions of Mediterranean or European waters. The results constitute the benchmark for benthic status in relation to trawling intensity in Eastern Mediterranean allowing to identify regions that are most at risk, and to prioritize management actions.